Identification of Interaction Hot Spots in Structures of Drug Targets on the Basis of Three‐Dimensional Activity Cliff Information. (30th July 2015) - Furtmann, Norbert; Hu, Ye; Gütschow, Michael; Bajorath, Jürgen
Abstract : Activity cliffs are defined as pairs or groups of structurally similar or analogous compounds that share the same specific activity but have large differences in potency. Although activity cliffs are mostly studied in medicinal chemistry at the level of molecular graphs, they can also be assessed by comparing compound binding modes. If such three‐dimensional activity cliffs (3D‐cliffs) are studied on the basis of X‐ray complex structures, experimental ligand–target interaction details can be taken into account. Rapid growth in the number of 3D‐cliffs that can be derived from X‐ray complex structures has made it possible to identify targets for which a substantial body of 3D‐cliff information is available. Activity cliffs are typically studied to identify structure–activity relationship determinants and aid in compound optimization. However, 3D‐cliff information can also be used to search for interaction hot spots and key residues, as reported herein. For six of seven drug targets for which more than 20 3D‐cliffs were available, series of 3D‐cliffs were identified that were consistently involved in interactions with different hot spots. These 3D‐cliffs often encoded chemical modifications resulting in interactions that were characteristic of highly potent compounds but absent in weakly potent ones, thus providing information for structure‐based design. Abstract : Three‐dimensional activity cliffs derived from X‐ray structures were systematically searched for recurrent interaction patterns that distinguished between highly and weakly potent compounds. For different drug targets, interaction hot spots were identified on the basis of detected interaction differences.